100 Top Cited COVID-19-related Publications - Hod, Rafidah; Idris, Idayu Badilla; Hod, Rozita (International Journal of Human and Health Sciences (IJHHS), 2022)
Objectives: Bibliometric analysis scrutinizes documents quantitatively using key parameters such as number of publications, subject area, citation metrics and collaborative networks. This study was conducted to answer these research questions: 1) What is the current publication trend globally on COVID-19?; 2) Which publications are in the top 100 most cited articles?; 3) Who are the most influential authors on COVID-19?; and 4) Which themes of COVID-19 are the most popular among scholars. Methods: A bibliometric search was conducted in Scopus database using keywords such as `COVID- 19’ or ‘COVID19’ or ‘COVID’ or ‘SARS-CoV-2’ in the article title. Document type was limited to original articles, review articles, conference papers and book chapters. A total of 139,888 documents were retrieved. The data is further analysed using Harzing’s Publish or Perish and VOSviewer to obtain the relevant citation metrics as well as visualization of collaborating networks. Results: Out of the total documents, 39% were published in the ‘Medicine’ subject area. Other subject areas include ‘Social Sciences’ (8.6%), ‘Computer Science’ (4%), ‘Engineering’ (3.1%) and ‘Psychology’ (2.8%). The most productive institution is Harvard Medical School which produced a total of 1921 documents. The top three leading countries are the United States, China and the United Kingdom, while the most productive author is Mahase, E. with 218 documents. The most influential publication, which had 11,279 citations, was titled `Clinical course and risk factors for mortality of adult inpatients with COVID-19 in Wuhan, China: a retrospective cohort study” published in The Lancet, 2020. The 100 top-cited publications have citations ranging from 802 – 11279. These top publications were published in 52 source titles, with the majority of the top-cited articles being published in The Lancet. Conclusion: Publications in COVID-19 are increasing exponentially and are mainly dominated by the United States. Extensive research is still ongoing, with more new discoveries in vaccine areas and related effects of COVID-19 are anticipated. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S46